PEKERJAAN STRUKTUR ATAP PADA PROYEK GEDUNG TERPADU PSIKOLOGI OLAHRAGA UNESA - Intan Imroatuzzakiyah (Jurnal Vokasi Teknik Sipil, 2024)
This activity was carried out in the construction project of the Integrated Sports Psychology Building of the State University of Surabaya which is located in Lidah Wetan, Surabaya. The project was carried out by PT. Nindya Karya as the implementing contractor with a project contract value of IDR 120,140,000,000 (Inches VAT). The project consists of two parts of the structure, namely the lower structure and the upper structure. The upper structure is a structure whose position is above the lower structure that is above the ground level such as a roof structure. There are several types of roof structures used, one of which is light steel and conventional steel. Light steel as a roof truss nowadays is increasingly popular, almost all buildings, offices, hospitals, places of worship, in big cities in Indonesia have used light steel roof trusses. The use factor of light steel structure is due to the ease and speed of installation.